DRIVERS OF TRUST AND PURCHASE INTENTION IN SOCIAL COMMERCE: A COMPREHENSIVE LITERATURE REVIEW - Dhaka, Parul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid expansion of social networking platforms and Web 2.0 technologies has transformed electronic commerce into social commerce, creating new opportunities for businesses and consumers. Social commerce integrates online shopping with social interactions, enabling trust-building mechanisms such as reviews, ratings, and recommendations. This study conducts a comprehensive literature review to examine the drivers of trust and their influence on purchase intention in social commerce. An extensive analysis of existing research highlights five key determinants of trust—perceived reputation, perceived size, economic benefit, service quality, and social commerce constructs. Findings suggest that trust is a critical factor in shaping consumer behaviour and remains a cornerstone of purchase intention in social commerce. The study further identifies challenges such as privacy concerns and information authenticity while outlining avenues for future research on cultural variations, consumer loyalty, and technological innovations.